PENGARUH SMART HAFIZ TERHADAP PENINGKATAN KEMAMPUAN MENGHAFAL Al-QUR’AN ANAK USIA DINI DI TAMAN KANAK-KANAK AL-WILDAN KOTA MAKASSAR - Hasri Ainun; Herlina; Usman Bafadal; Syamsuardi; Salma Samputri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT Smart hafiz is an audio-visual learning media that can be used to improve the ability to memorize the Al-Qur'an for young children. This research aims to determine the effect of smart hafiz on increasing the ability to memorize the Al-Qur'an for young children in Al-Wildan kindergarten, Makassar city. This research uses quantitative experimental methods. True experiments pre-test post-test control group design research design , with data collection techniques through observation, interviews, tests and documentation. The sampling technique uses probability sampling, simple random sampling. The research results obtained from the wilcoxon test showed that the asymp sig (2-tailed) .000 < 0.05 in the experimental group and the asymp sig (2-tailed), 001 < 0.05 in the control group, meaning that there was a significant influence on the use of smart hafiz towards increasing the ability to memorize the Al-Qur'an for early childhood in Al-Wildan kindergarten, Makassar city.